Assessment of attenuated Salmonella vaccine strains in controlling experimental Salmonella Typhimurium infection in chickens - Pei, Yanlong (Canadian Veterinary Medical Association, 2014)
Salmonella hold considerable promise as vaccine delivery vectors for heterologous antigens in chickens. Such vaccines have the potential additional benefit of also controlling Salmonella infection in immunized birds. As a way of selecting attenuated strains with optimal immunogenic potential as antigen delivery vectors, this study screened 20 novel Salmonella Typhimurium vaccine strains, differing in mutations associated with delayed antigen synthesis and delayed attenuation, for their efficacy in controlling colonization by virulent Salmonella Typhimurium, as well as for their persistence in the intestine and the spleen. Marked differences were observed between strains in these characteristics, which provide the basis for selection for further study as vaccine vectors.